UPAYA LKP HENNY'S DALAM MEMBERDAYAKAN REMAJA PEREMPUAN MELALUI KURSUS KETERAMPILAN TATA RIAS WAJAH DI KELURAHAN CIBABAT, CIMAHI TENGAH - Rohmalina Rohmalina; Megi Rahma Bungsu (IKIP Siliwangi, 2019)
This research is motivated by the existence of community problems around Cibabat Cimahi Utara area that still do not have knowledge and skill especially adolescent Woman so that they can improve their skill, skill, and professional self as stock to improve their economic quality. The purpose of this research is to describe the implementation of facial makeup course by LKP Henny's in order to empower the female teenager in Cibabat, North Cimahi. This research intends to describe data about Henny's LKP effort in empowering adolescent girls through Face Makeup course to prevent the soaring of Unemployment Rate among Young Women especially Young Women in Cibabat, North Cimahi. The theory used by the writer in this research are skill concept, LKP concept, management concept and PLS concept. The method used is the qualitative method. Data collection techniques used interview and observation methods. Location of research at LKP Henny's in Cibabat village, northern Cimahi. Based on the results of the discussion, LKP Henny's has applied empowerment of female adolescent in Cibabat area of North Cimahi in accordance with the indicators of community empowerment.